The role of affective teacher-student relationships in adolescents' school engagement and achievement trajectories. (October 2021) - Engels, Maaike C.; Spilt, Jantine; Denies, Katrijn; Verschueren, Karine
Abstract: This longitudinal study investigated the role of teacher-student closeness and conflict in adolescents' school engagement trajectories, and how school engagement dimensions predict achievement trajectories. A sample of 5, 382 adolescents ( M age.wave1 = 13.06, SD  = 0.51; 49.6% boys) were followed from Grade 7 to 9. Yearly measures included student reports on school engagement dimensions, teacher reports on closeness and conflict, and standardized tests for math achievement. Latent growth models revealed that closeness positively and conflict negatively predicted students' school engagement. Furthermore, adolescents' behavioral and emotional engagement, and disaffection in particular, played an important role in predicting achievement within the same schoolyear. Moreover, increases in behavioral disaffection and emotional engagement aligned with reduced and steeper increases in achievement between Grade 7 and 9, respectively. In general, this study underscores the importance of adolescents' affective teacher-student relationships for their engagement in school, and the role of school engagement in predicting achievement. Highlights: Teacher closeness contributed and conflict hampered adolescents' school engagement. School engagement dimensions had differential effects on achievement trajectories. Increases in behavioral disaffection aligned with reduced achievement in Grade 7–9. Increases in emotional engagement aligned with increased achievement in Grade 7–9.